2012
DOI: 10.1039/c2mb25100k
|View full text |Cite
|
Sign up to set email alerts
|

Robustness analysis of cellular systems using the genetic tug-of-war method

Abstract: Robustness is one of the principles of design inherent to biological systems. Cellular robustness can be measured as limits of intracellular parameters such as gene expression levels. We have recently developed an experimental approach coined as genetic Tug-Of-War (gTOW), which we used to perform robustness analysis in yeast. Using gTOW, we were able to measure the upper limit of expression of gene targets. In this review, we first elaborate on how the gTOW method compares to current mathematical simulation mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 48 publications
1
36
0
Order By: Relevance
“…Consistent with previous studies (Liu et al 1992), we found that introduction of a CEN plasmid carrying the actin-encoding gene ACT1 impaired cell proliferation The gTOW plasmid contains a gene under the control of its endogenous regulatory elements, a multicopy 2-µm origin, and the hypomorphic leu2-89 allele (a LEU2 gene with a truncated promoter) (Moriya et al 2012). (B-I) DSGs[5] on centromeric (CEN) plasmids were introduced into haploid wild-type (WT) cells.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…Consistent with previous studies (Liu et al 1992), we found that introduction of a CEN plasmid carrying the actin-encoding gene ACT1 impaired cell proliferation The gTOW plasmid contains a gene under the control of its endogenous regulatory elements, a multicopy 2-µm origin, and the hypomorphic leu2-89 allele (a LEU2 gene with a truncated promoter) (Moriya et al 2012). (B-I) DSGs[5] on centromeric (CEN) plasmids were introduced into haploid wild-type (WT) cells.…”
Section: Resultssupporting
confidence: 80%
“…For gTOW, the gene of interest and its regulatory elements are present on a plasmid that can reach a high copy number to promote cell growth in medium lacking leucine due to the presence of a hypomorphic LEU2 allele (leu2-89) ( Fig. 1A; Moriya et al 2012). However, toxicity of the gene of interest prevents attaining high copy number even in growth conditions that select for the presence of the plasmid.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As gTOW increases the copy number of the target gene with its native promoter, this argument is possible. We thus consider that gTOW is a useful method for evaluating the robustness of cellular systems by assessing how much gene expression is fluctuated from the native level when the system halts (Moriya et al 2012). The advantage of gTOW is that one cannot only isolate genes causing cellular dysfunctions upon overexpression but also quantitate the limits of gene overexpression that are associated with cellular robustness.…”
mentioning
confidence: 99%
“…We previously developed the genetic tug-of-war (gTOW) method to measure the limit of gene overexpression (Moriya et al 2006(Moriya et al , 2011(Moriya et al , 2012. Using gTOW, we can assess the limit of gene overexpression as the copy number limit (CNL) of the target gene as follows.…”
mentioning
confidence: 99%